UPAYA MENINGKATKAN HASIL BELAJAR IPA MENGGUNAKAN MEDIA SOSIAL TIKTOK SEBAGAI MEDIA PEMBELAJARAN - Musfiqoh, Riqotul; Nuruddin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement of science learning outcomes through the use of TikTok social media as learning medium. This study uses a quantitative approach with the method used being a Quasi Eksperimental model One Group Pre-test Post-test. The research subjects consisted of one class. Data collection was carried out in the form Pre-test and Post-test to determine student’s abilities before and after the application of TikTok social media as a learning medium. The data obtained were analyzed using descriptive statistical analysis. The results of the study indicate that the use of TikTok social media in learning activities can improve student learning outcomes. The can be seen in the increase in student’s average score after being given treatment using TikTok social media compared to before using the media. Therefore, the researcher learning media that is interesting and effective in improving learning outcomes.